Wege zur Finanzierung der öffentlichen Infrastruktur - Marcel Fratzscher; Holger Mühlenkamp; Fabian Lindner; Katja Rietzler; Bastian Alm; Jeromin Zettelmeyer; Gerd Landsberg (Wirtschaftsdienst, 2015)
Im April 2015 hat die Expertenkommission zur 'Stärkung von Investitionen in Deutschland' ihren Bericht abgeliefert und damit die Diskussion über die Finanzierung der öffentlichen Infrastruktur in Deutschland wieder angeregt. Einig sind sich die Autoren über den dringenden Investitionsbedarf - vor allem bei den Kommunen. Kontrovers ist, inwieweit private Investoren gewonnen werden können oder sollten, welche Kosten damit verbunden sind und ob sich die Finanzierungsmethode auf die Einhaltung der Schuldenbremse auswirkt. – – It is an established fact that Germany has to invest more in its infrastructure. This is particularly true at the municipal level. The federal government acknowledges this, but its measures remain insufficient. Public-private partnerships have a bad reputation, but a survey of municipality treasurers finds that they do not view PPPs as inefficient, as two authors of the German Finance Ministry state. The report by the commission of experts on encouraging investments in Germany offers solutions, but some authors do not consider them viable. They find that the main recommendations of the commission would lead to the inefficient allocation of risk, an unnecessary burden on the public budget and the declining transparency of public debt.
Keywords: H23; H54; L92; R42; R48; 330; Infrastrukturinvestition; Infrastrukturfinanzierung; Infrastrukturpolitik; Deutschland